2016
DOI: 10.1002/jlcr.3379
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and preliminary biological evaluation of a new 18F‐labeled triethylene glycol derivative of triphenylphosphonium

Abstract: Delocalized lipophilic cations such as [(18)F]fluorobenzyltriphenylphosphonium ([(18)F]FBnTP) can accumulate in mitochondria and have been used in myocardial perfusion imaging (MPI). In this study, we established a simplified method for [(18)F]FBnTP synthesis using triphenylphosphine hydrobromide (PPh3 •HBr) without preparing an intermediate that contains benzyl bromide structure. Applying this new method, we synthesized and evaluated a novel (18)F-labeled PEGylated BnTP derivative ([(18)F]FPEGBnTP). In vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Changes in [ 18 F]FBnTP uptake may be difficult to interpret since the accumulation of this tracer can be affected by cellular efflux processes driven by multidrug‐resistance proteins and by tissue‐dependent differences of background uptake. Various structural analogs of [ 18 F]FBnTP have also been prepared, such as 4‐[ 18 F]‐tetraphenylphosphonium (TPP), ([ 18 F]fluoropentyl)triphenylphosphonium, and [ 18 F]PEGylated‐BnTP . Uptake of these compounds is probably affected by the same processes as the tissue uptake of [ 18 F]FBnTP.…”
Section: Cell Death Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in [ 18 F]FBnTP uptake may be difficult to interpret since the accumulation of this tracer can be affected by cellular efflux processes driven by multidrug‐resistance proteins and by tissue‐dependent differences of background uptake. Various structural analogs of [ 18 F]FBnTP have also been prepared, such as 4‐[ 18 F]‐tetraphenylphosphonium (TPP), ([ 18 F]fluoropentyl)triphenylphosphonium, and [ 18 F]PEGylated‐BnTP . Uptake of these compounds is probably affected by the same processes as the tissue uptake of [ 18 F]FBnTP.…”
Section: Cell Death Imagingmentioning
confidence: 99%
“…235 The signal of the tracer has been reported to be stable up to 45 min after injection. 236 Changes in [ 18 F]FBnTP uptake may be difficult to interpret since the accumulation of this tracer can be affected by cellular efflux processes driven by multidrug-resistance proteins 237 242 Uptake of these compounds is probably affected by the same processes as the tissue uptake of [ 18 F]FBnTP.…”
Section: [ 18 F]fluorobenzyl Triphenyl Phosphoniummentioning
confidence: 99%
“…Recently, Ravert et al reduced the amount of reagents and synthesis time for the first 3 reaction steps by using microwave‐assisted heating . Tominaga et al reported the direct coupling of 4‐[ 18 F]fluorobenzyl alcohol with PPh 3 ·HBr to form 18 F‐FBnTP (Figure ), and the overall number of reaction steps was reduced to 3 . However, such multistep approach remains a challenge for implementing the synthesis of 18 F‐FBnTP for routine clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis procedures for the preparation of 18 F‐FBnTP reported by A, Ravert et al; B, Tominaga et al; and C, this study…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation